2023
DOI: 10.1126/scitranslmed.abp9952
|View full text |Cite
|
Sign up to set email alerts
|

SGLT2 inhibitor ameliorates endothelial dysfunction associated with the common ALDH2 alcohol flushing variant

Abstract: The common aldehyde dehydrogenase 2 ( ALDH2 ) alcohol flushing variant known as ALDH2*2 affects ∼8% of the world’s population. Even in heterozygous carriers, this missense variant leads to a severe loss of ALDH2 enzymatic activity and has been linked to an increased risk of coronary artery disease (CAD). Endothelial cell (EC) dysfunction plays a determining role in all stages of CAD pathogenesis, including early-onset CAD. However, the contribution of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 91 publications
0
15
0
Order By: Relevance
“…ALDH2 also potentially interacts with tubular transporters. Empagliflozin, an SGLT2 inhibitor, can mitigate ALDH2*2-induced endothelial cell dysfunction with the best docking pose with Alda-1 through the inhibition of Na + /H + exchanger 1 (NHE-1) and activation of AKT kinase and endothelial NO synthase pathways [ 96 ]. While tubular transporters play a significant role in rare tubulointerstitial diseases, there is little research investigating the involvement of ALDH2 in these conditions.…”
Section: Mitochondria Disorder In Rare Tubulointerstitial Diseases An...mentioning
confidence: 99%
“…ALDH2 also potentially interacts with tubular transporters. Empagliflozin, an SGLT2 inhibitor, can mitigate ALDH2*2-induced endothelial cell dysfunction with the best docking pose with Alda-1 through the inhibition of Na + /H + exchanger 1 (NHE-1) and activation of AKT kinase and endothelial NO synthase pathways [ 96 ]. While tubular transporters play a significant role in rare tubulointerstitial diseases, there is little research investigating the involvement of ALDH2 in these conditions.…”
Section: Mitochondria Disorder In Rare Tubulointerstitial Diseases An...mentioning
confidence: 99%
“…Another study demonstrated that DAPA reduces cardiac endothelial dysfunction and microvascular injury by inhibition of the XO/sarco(endo) plasmic reticulum calcium ATPase 2/calmodulin-dependent kinase II/coffilin pathway in I/R injury mice ( 170 ). EMPA also improves endothelial cell dysfunction induced by a mutant aldehyde dehydrogenase 2 unable to metabolize acetaldehyde by inhibiting NHE1 and activating the AKT kinase and eNOS pathways ( 171 ). EMPA attenuates cardiac microvascular I/R injury through the activation of the AMP-activated protein kinase α1 (AMPKα1)/UNC-52-like kinase 1/FUN14 domain containing 1/mitophagy pathway ( 172 ).…”
Section: Role Of Sglt2is In Cellular Pathophysiological Processesmentioning
confidence: 99%
“…to find a compound that mitigates reactive oxidative species and boosts nitric oxide in iPSC-derived ECs with alcohol dehydrogenase 2 ( ALDH2∗2 rs671) variant, leading to drug repurposing of the sodium glucose cotransporter-2 inhibitor, empagliflozin. 64 …”
Section: Introductionmentioning
confidence: 99%
“…Thus, coronary EC dysfunction is a well-recognized maladaptive process in the development of CAD from early initiation to end-stage atherothrombotic complication. 64 Mutations in alcohol dehydrogenase 2 ( ALDH2 , also named ALDH2∗2 rs671), which are prevalent in East Asian populations and manifest as an “alcohol flush,” are also associated with an increased risk of CAD. 64 , 96 Using patient-derived ALDH2∗2 rs671 iPSC-ECs, Guo et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation